Plasma soluble leptin receptor levels are associated with pancreatic β‐cell dysfunction in patients with type 2 diabetes - Morioka, Tomoaki (J Diabetes Investig, 2017)
AIMS/INTRODUCTION: A soluble form of the leptin receptor (soluble Ob‐R) in the circulation regulates leptin's bioactivity, and is inversely associated with body adiposity and circulating leptin levels. However, no study has examined the clinical impact of soluble Ob‐R on glucose metabolism in diabetes. The present study aimed to investigate the association of plasma soluble Ob‐R levels with insulin resistance and pancreatic β‐cell function in patients with type 2 diabetes. MATERIALS AND METHODS: A total of 289 Japanese patients with type 2 diabetes were included in the present study. Fasting plasma soluble Ob‐R levels and plasma leptin levels were measured by enzyme‐linked immunosorbent assay. Insulin resistance and pancreatic β‐cell function were estimated by homeostasis model assessment of insulin resistance, homeostasis model assessment of β‐cell function and fasting C‐peptide index. RESULTS: The median plasma soluble Ob‐R level and plasma leptin level were 3.4 ng/mL and 23.6 ng/mL, respectively. Plasma soluble Ob‐R levels were negatively correlated with homeostasis model assessment of insulin resistance, homeostasis model assessment of β‐cell function and the C‐peptide index, whereas plasma leptin levels were positively correlated with each index in univariate analyses. Multivariate analyses including plasma soluble Ob‐R levels, plasma leptin levels and use of sulfonylureas, along with age, sex, body mass index and other covariates, showed that soluble Ob‐R levels were independently and negatively associated with homeostasis model assessment of β‐cell function and the C‐peptide index, but not significantly associated with homeostasis model assessment of insulin resistance. CONCLUSIONS: Plasma soluble Ob‐R levels are independently associated with pancreatic β‐cell function, but not with insulin resistance, in patients with type 2 diabetes. The present study implicates the role of soluble Ob‐R in pancreatic β‐cell dysfunction in type 2 diabetes.